Synthesis of sialic acid conjugates of the clinical near-infrared dye as next-generation theranostics for cancer phototherapy. Issue 6 (21st January 2022) - Dong, Huiling; Gao, Yanan; Huang, Xuefei; Wu, Xuanjun
Abstract : The next generation of cancer theranostics based on Sia–ICG produced by the conjugation of sialic acid with indocyanine green (ICG) has been developed. Administration of Sia–ICG plus laser irradiation resulted in excellent ablation of solid tumors. Abstract : Cancer is a multifaceted global health problem that requires continuous action to develop next-generation cancer theranostics. Inspired by the emerging use of indocyanine green (ICG), the only clinically approved near-infrared (NIR) dye for cancer phototherapy, here we synthesized two ICG conjugate theranostics by coupling ICG to sialic acid (Sia) through the C2 and C9 positions of Sia, respectively, referred to as Sia-C2–ICG and Sia-C9–ICG. Encouragingly, Sia-C2/C9–ICGs show superior in vitro properties, including enhanced stability, reduced non-specific binding to serum proteins, and improved blood compatibility, highlighting the benefits of Sia coupling. Notably, in vivo NIR imaging shows that Sia-C9–ICG significantly promotes tumor targeting and effectively prolongs the circulation time in the body, while Sia-C2–ICG is superior to ICG but inferior to Sia-C9–ICG in targeting tumors. Furthermore, Sia-C9–ICG combined with NIR laser irradiation can lead to excellent photothermal and photodynamic therapies for cancer cells, resulting in superior solid tumor ablation. To our knowledge, this is the first report of Sia–NIR conjugates achieving significant tumor reduction in vivo . Together, these advances render Sia-C9–ICG an attractive lead as next-generation cancer theranostics that can be translated clinically to treat human patients.